Detailed simulation of morphodynamics: 2. Sediment pickup, transport, and deposition. Issue 8 (7th August 2013) - Nabi, M.; de, H. J.; Mosselman, E.; Sloff, C. J.; Shimizu, Y.
<x xml:space="preserve">Abstract</x> [1] The paper describes a numerical model for simulating sediment transport with eddy‐resolving 3‐D models. This sediment model consists of four submodels: pickup, transport over the bed, transport in the water column and deposition, all based on a turbulent flow model using large‐eddy simulation. The sediment is considered as uniform rigid spherical particles. This is usually a valid assumption for sand‐bed rivers where underwater dune formation is most prominent. Under certain shear stress conditions, these particles are picked up from the bed due to an imbalance of gravity and flow forces. They either roll and slide on the bed in a sheet of sediment or separate from the bed and get suspended in the flow. Sooner or later, the suspended particles settle on the bed again. Each of these steps is modeled separately, yielding a physics‐based process model for sediment transport, suitable for the simulation of bed morphodynamics. The sediment model is validated with theoretical findings such as the Rouse profile as well as with empirical relations of sediment bed load and suspended load transport. The current model shows good agreement with these theoretical and empirical relations. Moreover, the saltation mechanism is simulated, and the average saltation length, height, and velocity are found to be in good agreement with experimental results.